Two-dimensional fluorine-doped carbon nanosheet and preparation and application thereof

By adding two-dimensional fluorine-doped carbon nanosheets prepared by the negative electrode plate of the lead-acid battery, the problem of the negative electrode cycle capacity of the lead-acid battery in a high-ratio partial charging state is solved, and the effect of improving the conductivity and extending the cycle life is achieved.

CN119706808AActive Publication Date: 2025-03-28DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311261790.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-03-28
Estimated Expiration
2043-09-27

AI Technical Summary

Technical Problem

The negative electrode circulation capacity of lead-acid batteries dropped sharply under the high-ratio partial charging state. The main reason is that the gradual accumulation of lead sulfate crystals with no chemical activity on the surface of the negative electrode, resulting in sulfation.

Method used

Two-dimensional fluorine-doped carbon nanosheets with transverse sizes of microns were prepared by the hard template method, and they were incorporated into the negative electrode plate of the lead-carbon battery to inhibit the hydrogen evolution reaction, improve the conductivity, and promote the electrochemical reduction of lead sulfate.

Benefits of technology

It significantly improves the conductivity of the negative electrode plate in the discharge state, increases the charging and receiving current, inhibits sulfation, and extends the cycle life of the lead-carbon battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004473177440000101
    Figure BDA0004473177440000101
  • Figure BDA0004473177440000111
    Figure BDA0004473177440000111
  • Figure BDA0004473177440000112
    Figure BDA0004473177440000112
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a two-dimensional fluorine-doped carbon nanosheet. The preparation method of the two-dimensional fluorine-doped carbon nanosheet comprises the following steps: a) synthesizing a hard template organic metal framework ZIF-L nanosheet, dispersing the nanosheet in an ethanol water solution, sequentially adding a cationic surface active agent, resorcinol, a fluorine-containing monomer, ammonia water and a formaldehyde solution into the dispersion liquid, reacting, centrifuging and drying to obtain a ZIF-L at fluorine-doped phenolic resin composite nanosheet; and b) roasting the composite nanosheet to obtain the two-dimensional fluorine-doped carbon nanosheet. The micron-scale two-dimensional fluorine-doped carbon nanosheet is prepared through a hard template method, fluorine doping inhibits a hydrogen evolution reaction, the micron-scale transverse size endows the nanosheet with long-range conductivity, the conductivity of a negative plate in a discharge state is improved, polarization is relieved, the charge receiving current is increased, electrochemical reduction of lead sulfate to metal lead is promoted, sulfation is inhibited, and the performance of a lithium ion battery is improved. And finally, the cycle life of the lead-carbon battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a preparation method and application of a two-dimensional fluorine-doped carbon nanosheet, and belongs to the field of lead-carbon batteries and lead-acid batteries. Background Art

[0002] Lead-acid batteries are a long-standing and widely used energy storage technology. Due to more stringent performance requirements in various application scenarios (such as automobiles and large-scale energy storage), lead-acid batteries are facing the need for improved performance. In particular, under high-rate partial state of charge (HRPSoC) load, the negative electrode is considered to be the main reason for the sharp drop in cycle capacity. The capacity decay is mainly attributed to the gradual accumulation of chemically inactive lead sulfate crystals on the surface of the negative electrode, especially at the bottom, i.e. sulfation. The reason is that the lead sulfate cannot be fully and effectively converted into sponge lead during the subsequent charging process.

[0003] By doping the negative electrode with up to ten times the amount of carbon material usually added, the irreversible sulfation phenomenon of lead-acid batteries can be significantly suppressed. At this time, it is called a "lead-carbon battery". Moseley summarized the role of carbon in the negative electrode. Among the different possible functions, carbon may promote lead nucleation. Pavlov confirmed that the electrochemical reduction of lead sulfate occurs preferentially on the surface of electrochemically active carbon. In addition, carbon can also serve as a steric hindrance to the crystallization of lead sulfate so that it maintains a high specific surface area. Activated carbon increases the porosity of the negative electrode by providing an additional structural skeleton, promoting the migration of the electrolyte from the surface to the interior. As a result, sufficient sulfuric acid can be provided to match the electrode reaction.

[0004] When the lead-carbon battery is charged, while the basic electrode reaction occurs at the negative electrode, due to the low hydrogen evolution potential of the carbon material, the hydrogen evolution reaction (HER) on the surface of the carbon material is accompanied. The hydrogen evolution reaction not only reduces the coulombic efficiency but also cuts off the conductive connection between the lead and the carbon particles. By loading a variety of high hydrogen evolution overpotential materials, such as lead and its derivatives, indium oxide, gallium oxide, bismuth oxide, etc., the accompanying adverse effects can be alleviated. Alternatively, doping with other atoms, such as pyrrolic nitrogen, oxygen, boron, phosphorus, etc., has been proven to be an effective method for inhibiting hydrogen evolution. However, the electronegativity of the above-mentioned doping elements is far less than that of fluorine, that is, the effect of inhibiting the hydrogen evolution reaction is not as good as that of fluorine.

[0005] Given that the size of the carbon materials currently added to the negative electrode plates is generally a few hundred nanometers, the conductivity of the negative electrode plates in the discharge state is limited.

[0006] The present invention incorporates two-dimensional fluorine-doped carbon nanosheets with a lateral size of several microns into the negative plate of a lead-carbon battery, which significantly improves the conductivity of the negative plate in a discharged state, thereby increasing the charging receiving current, promoting the electroreduction conversion of lead sulfate crystals to sponge lead, inhibiting sulfation, and extending the battery cycle life. Summary of the invention

[0007] Two-dimensional fluorine-doped carbon nanosheets with a lateral size of several microns were prepared by the hard template method. Fluorine doping inhibits the hydrogen evolution reaction, and the micron-level size gives it long-range conductivity, which improves the conductivity of the negative plate in the discharged state, reduces polarization, increases the charging receiving current, promotes the electrochemical reduction of lead sulfate to metallic lead, inhibits sulfation, and thus extends the cycle life of the lead-carbon battery.

[0008] According to one aspect of the present invention, a method for preparing a two-dimensional fluorine-doped carbon nanosheet is provided, comprising the following steps:

[0009] a) firstly synthesizing a hard template metal organic framework ZIF-L nanosheet, dispersing it in an ethanol aqueous solution, sequentially adding a cationic surfactant, resorcinol, a fluorinated monomer, ammonia water and a formaldehyde solution to the above dispersion, reacting, centrifuging and drying to obtain a powder;

[0010] b) calcining the powder to obtain two-dimensional fluorine-doped carbon nanosheets.

[0011] The above reaction is carried out in a glass container, the centrifugation is carried out in a centrifuge, and the powder is placed in an open quartz boat and transferred to a tube furnace for calcination.

[0012] Optionally, the cationic surfactant is selected from at least one of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, cetylpyridinium bromide, dodecyltrimethylammonium bromide and tributylhexadecylphosphonium bromide.

[0013] Optionally, the fluorine-containing monomer is selected from at least one of 4-fluorophenol, 3-fluorophenol, 3-(trifluoromethoxy)phenol and 4-(trifluoromethyl)phenol.

[0014] Optionally, the mass ratio of the cationic surfactant, resorcinol, fluorine-containing monomer, ammonia water and formaldehyde solution is 1:1-2:0.1-1:3-5:1-3.

[0015] Optionally, the mass ratio of the cationic surfactant, resorcinol, fluorine-containing monomer, ammonia water and formaldehyde solution is any value in the range of 1:1-2:0.1-1:3-5:1-3 or a range between two values.

[0016] Optionally, the reaction temperature is 15 to 50° C., and the reaction time is 6 to 10 hours.

[0017] Optionally, the reaction temperature is any value of 15°C, 25°C, 50°C, or a range between these two values.

[0018] Optionally, the reaction time is any value among 6h, 8h, 10h, or a range value between two values.

[0019] Optionally, the centrifugal speed is 2000-5000 rpm, and the centrifugal time is 2-10 min.

[0020] Optionally, the centrifugal rotation speed is any value among 2000 rpm, 3000 rpm, 5000 rpm, or a range value between the two values.

[0021] Optionally, the centrifugation time is any value among 2 min, 6 min, 10 min, or a range value between the two values.

[0022] Optionally, the drying temperature is 60 to 100° C., and the drying time is 24 to 36 hours.

[0023] Optionally, the drying temperature is any value among 60°C, 80°C, 100°C, or a range between these two values.

[0024] Optionally, the drying time is any value among 24h, 30h, 36h, or a range value between two values.

[0025] Optionally, the roasting includes a one-stage roasting;

[0026] The temperature of the first stage of roasting is 800-1000° C., and the time of the first stage of roasting is 2-4 hours.

[0027] Optionally, the temperature of the first stage calcination is any value among 800°C, 900°C, 1000°C, or a range between these two values.

[0028] Optionally, the temperature of the first stage roasting is any value among 2h, 3h, 4h, or a range value between two values.

[0029] According to another aspect of the present invention, there is provided a method for applying the two-dimensional fluorine-doped carbon nanosheets obtained according to the above preparation method in a negative electrode plate of a lead-carbon battery, comprising the following steps:

[0030] Step 1: adding water and sulfuric acid to a mixture containing two-dimensional fluorine-doped carbon nanosheets, additives, short fibers and lead powder, and stirring to obtain a lead paste;

[0031] Step 2: Press the lead paste onto the grid, solidify it, and dry it to obtain the negative electrode plate of the lead-carbon battery.

[0032] Optionally, the mass ratio of the two-dimensional fluorine-doped carbon nanosheets, additives, short fibers and lead powder is 1.5:1.4-1.6:0.06-0.08:100-150.

[0033] Optionally, the mass ratio of the two-dimensional fluorine-doped carbon nanosheets, additives, short fibers and lead powder is any value of 1.5:1.4:0.06:100, 1.5:1.5:0.07:125, 1.5:1.6:0.08:150, or a range value between two values.

[0034] Optionally, the water accounts for 13% to 20% of the mass of the mixture; the sulfuric acid accounts for 7% to 12% of the mass of the mixture, and the density of the sulfuric acid is 1.4 g cm -3 .

[0035] Optionally, the curing temperature is 45 to 55° C., and the curing time is 40 to 60 hours.

[0036] Optionally, the curing temperature is any value of 45° C., 50° C., 55° C., or a range between these two values.

[0037] Optionally, the curing time is any value among 40h, 50h, 60h, or a range value between two values.

[0038] Optionally, the temperature of the drying I is 60 to 85° C., and the drying time is 9 to 20 hours.

[0039] Optionally, the drying temperature I is any value among 60°C, 70°C, 85°C, or a range between these two values.

[0040] Optionally, the drying time I is any value among 9h, 15h, 20h, or a range value between two values.

[0041] Optionally, the lead paste has a thickness of 2 to 4 mm.

[0042] The present invention prepares micrometer-scale two-dimensional fluorine-doped carbon nanosheets by a hard template method. Fluorine doping inhibits hydrogen evolution reaction. The micrometer-scale lateral size gives it long-range conductivity, improves the conductivity of the negative plate in the discharge state, reduces polarization, increases the charging receiving current, promotes the electrochemical reduction of lead sulfate to metallic lead, inhibits sulfation, and ultimately prolongs the cycle life of the lead-carbon battery.

[0043] The beneficial effects that the present invention can produce include:

[0044] 1) The preparation method provided by the present invention, in which two-dimensional fluorine-doped carbon nanosheets are prepared by a hard template method, significantly improves the long-range conductivity of carbon materials compared with carbon nanoparticles, reduces the ohmic polarization of the battery, increases the charging receiving current, alleviates the sulfation of the negative plate, and greatly extends the cycle life of the lead-carbon battery.

[0045] 2) The lead-carbon battery negative electrode plate provided by the present invention has better charge and discharge reversibility and charge acceptance capacity than the composite negative electrode plate prepared from two-dimensional carbon nanosheets and mesoporous carbon nanoparticles. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 Schematic diagram of the synthesis of two-dimensional fluorine-doped carbon nanosheets (Example 1)

[0047] Figure 2 SEM images of ZIF-L, ZIF-L@PR and ZIF-L@FPR and their carbonized products (A) ZIF-L nanosheets (B) ZIF-L@PR (C) ZIF-L@FPR (D) Carbon materials derived from ZIF-L (E) Two-dimensional carbon nanosheets (2D C) (F) Two-dimensional fluorine-doped carbon nanosheets (2D FC) (Example 1 and Comparative Example 1)

[0048] Figure 3 Cyclic voltammogram (Example 1 and Comparative Example 1)

[0049] Figure 4 Electrochemical impedance spectroscopy (Example 1 and Comparative Example 1)

[0050] Figure 5 Coulombic efficiency and voltage efficiency (Example 1 and Comparative Example 1)

[0051] Figure 6 Energy efficiency (Example 1 and Comparative Example 1)

[0052] Figure 7 Discharge capacity change (Example 1 and Comparative Example 1)

[0053] Figure 8 SEM images of negative electrode plates doped with 2D carbon nanosheets and 2D fluorine-doped carbon nanosheets (A) 2D C-top-surface (B) 2D FC-top-surface (C) 2D C-top-inside (D) 2D FC-top-inside

[0054] Fig. 9 XRD patterns of the top of the negative electrode plate doped with 2D carbon nanosheets and 2D fluorine-doped carbon nanosheets (A) 2D C-top of the negative electrode plate (B) 2D FC-top of the negative electrode plate (C) Pb standard card (D) PbSO4 standard card

[0055] Table 1 Ratio of raw materials for preparing two-dimensional carbon nanosheets and two-dimensional fluorine-doped carbon nanosheet precursors

[0056] Table 2 Charging receiving current of lead-carbon battery with negative plate doped with two-dimensional carbon nanosheets, two-dimensional fluorine-doped carbon nanosheets and mesoporous fluorine-doped carbon nanoparticles

[0057] Table 3 Hydrogen evolution reaction of lead-carbon battery with rated capacity of 5.7Ah DETAILED DESCRIPTION

[0058] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0059] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0060] Example 1

[0061] At room temperature, 7.35 g Zn(NO3)2·6H2O was dissolved in 500 mL deionized water, and 16.25 g 2-methylimidazole (Hmim) was dissolved in 500 mL deionized water. The Hmim aqueous solution and Zn(NO3)2 aqueous solution were obtained by magnetic stirring for 0.5 h. The molar ratio of Zn in the two solutions was 2+ :Hmim=1:8. The Hmim aqueous solution was quickly poured into the Zn(NO3)2 aqueous solution, and the solution instantly turned milky white. After stirring for 0.5h, a large amount of white floccules appeared, and stirring was continued for 3.5h (the total reaction time was controlled at 4.0h). After the reaction was completed, the elliptical metal organic framework ZIF-L nanosheets were separated by centrifuge at a speed of 5000rpm for 3.0min.

[0062] 3.5g ZIF-L nanosheets were dispersed in a mixed solution of ethanol and water (150mL ethanol + 350mL water), stirred for 0.5h, then 0.35g hexadecyltrimethylammonium bromide (CTAB) was added, and stirring continued for 0.5h. In order to allow CTAB to be fully adsorbed on the surface of the ZIF-L nanosheets, 0.6125g resorcinol, 0.208g 4-fluorophenol, and 1.75mL 28wt% ammonia water were added in sequence, and magnetic stirring was performed for 0.5h. Finally, 0.90mL 37-40wt% formaldehyde aqueous solution was added with a pipette. The reaction was continued for 8.0h, and a layer of fluorine-doped phenolic resin (FPR-1) was coated on the surface of the ZIF-L nanosheets. A sufficient amount of ZIF-L@FPR-1 composite nanosheets was synthesized, separated by vacuum membrane filtration, and transferred to a 70°C oven for drying for 24h, and the dried ZIF-L@FPR-1 composite nanosheets ( Figure 2 C). Place the sample in an open quartz container and transfer it to a tube furnace. In a nitrogen inert atmosphere, heat the mixture at 5°C min -1 The heating rate was increased from room temperature to 800°C, kept at 800°C for 2.0 h, and then naturally cooled to room temperature to obtain a two-dimensional fluorine-doped carbon nanosheet-1.

[0063] The ball-milled lead oxide powder, two-dimensional fluorine-doped carbon nanosheets-1 (1.5wt%, relative to the mass of the ball-milled lead oxide powder), polyester staple fibers with a length of 3 to 5 mm (0.06wt%, relative to the mass of the ball-milled lead oxide powder, polyester PET fibers), barium sulfate (1.2wt%, relative to the mass of the ball-milled lead oxide powder), and lignin (0.2wt%, relative to the mass of the ball-milled lead oxide powder) were placed in a blender and stirred thoroughly to mix the components evenly. Subsequently, the above mixture was poured into a paste machine, and deionized water (13.3wt%, relative to the mass of the ball-milled lead oxide powder) was first slowly added, and then 1.4g cm -3 H2SO4 solution (25°C) was added and stirred for 25 min to obtain lead paste. The lead paste was manually pressed on both sides of the 57.0 mm × 38.0 mm (length × width) lead-calcium alloy grid to ensure that the lead paste was wrapped around it. The factory-coated board paper was used to sandwich it in the middle and rolled flat with a hard plastic tube. The quality was controlled at 0.71 g cm -2 . After coating, the wet negative plate is transferred to a constant temperature and humidity chamber for curing and drying. The curing procedure is 95% relative humidity, 45°C for 36h, 70% relative humidity, 45°C for 2h, 50% relative humidity, 45°C for 2h; the drying procedure is 60°C for 0.5h, 70°C for 0.5h, 85°C for 8.0h, and the negative plate is obtained. For each 2V test battery, four negative plates (length × width × thickness = 57.0mm × 38.0mm × 2.0mm) are paired with three positive plates purchased from Baoding Fengfan Group Co., Ltd. (length × width × thickness = 57.0mm × 42.0mm × 2.0mm), which are alternately stacked in sequence. Each positive and negative plate is wrapped with a 1.5mm thick absorbed glass fiber mat diaphragm (AGM), and the AGM compression ratio of the battery is 20% after the battery is assembled. Afterwards, 80.3 g of 1.275 g cm was poured into the battery (60.0 mm long × 30.2 mm wide × 70.4 mm high) using vacuum assistance. -3 Sulfuric acid solution (25 °C) was used to immerse the positive and negative plates and the separator. Before the electrochemical test, the lead-carbon battery was charged and discharged at a fixed rate constant current. The specific process was to stand for 40 minutes, charge at 3.0V constant voltage for 10 seconds, charge at 901.3mA constant current for 18 hours, discharge at 901.3mA constant current for 3 hours, charge at 901.3mA constant current for 10 hours, discharge at 901.3mA constant current for 4 hours, charge at 901.3mA constant current for 9.5 hours, and finally stand for 1 minute. The cyclic voltammetry test was performed on an electrochemical workstation (BioLogic, VMP-300) with a scanning voltage range of 0.0 to -1.5V (relative to the Hg / Hg2SO4 reference electrode) and a scanning rate of 10mV s -1The electrochemical impedance spectroscopy test was also performed on an electrochemical workstation (BioLogic, VMP-300) with a frequency range of 100kHz to 0.1Hz and a voltage amplitude of 10mV. The constant current charge and discharge test was performed using a battery tester (CT2001A, 5V / 2A, LANHE), with the charge and discharge cut-off voltages of 2.4V and 1.8V, respectively.

[0064] Example 2

[0065] At room temperature, 7.35 g Zn(NO3)2·6H2O was dissolved in 500 mL deionized water, and 16.25 g Hmim was dissolved in 500 mL deionized water. The mixture was stirred magnetically for 0.5 h until fully dissolved. The molar ratio of Zn 2+ :Hmim=1:8. The Hmim aqueous solution was quickly poured into the Zn(NO3)2 aqueous solution, and the solution instantly turned milky white. After stirring for 0.5h, a large amount of white floccules appeared, and the total reaction time was controlled at 4.0h. After the reaction was completed, the ZIF-L nanosheets were separated by a centrifuge at a speed of 5000rpm for 3.0min.

[0066] 3.5g ZIF-L nanosheets were dispersed in a mixed solution of ethanol and water (150mL ethanol + 350mL water), stirred for 0.5h, then 0.35g hexadecyltrimethylammonium bromide (CTAB) was added, and stirring continued for 0.5h. In order to allow CTAB to be fully adsorbed on the surface of ZIF-L nanosheets, 0.652g resorcinol, 0.166g 4-fluorophenol, 1.75mL≥28% ammonia water were added in sequence, magnetic stirring was continued for 0.5h, and finally 0.90mL 37-40% formaldehyde aqueous solution was added with a pipette. The reaction was continued for 8.0h, and a layer of fluorine-doped phenolic resin (FPR-2) was coated on the surface of ZIF-L nanosheets. Sufficient ZIF-L@FPR-2 composite nanosheets were synthesized, separated by vacuum membrane filtration, transferred to a 70℃ oven for drying for 24h, and dried ZIF-L@FPR-2 composite nanosheets were collected. Place the sample in an open quartz container and transfer it to a tube furnace. In a nitrogen inert atmosphere, heat the sample at 5 °C min -1 The heating rate was from room temperature to 800° C., kept at 800° C. for 2.0 h, and then naturally cooled to room temperature to obtain a two-dimensional fluorine-doped carbon nanosheet-2. Other implementation steps and methods were the same as those in Example 1.

[0067] Example 3

[0068] At room temperature, 7.35 g Zn(NO3)2·6H2O was dissolved in 500 mL deionized water, and 16.25 g Hmim was dissolved in 500 mL deionized water. The mixture was stirred magnetically for 0.5 h until fully dissolved. The molar ratio of Zn 2+:Hmim=1:8. The Hmim aqueous solution was quickly poured into the Zn(NO3)2 aqueous solution, and the solution instantly turned milky white. After stirring for 0.5h, a large amount of white floccules appeared. The total reaction time was controlled within 1.0h to obtain smaller ZIF-L nanosheets. After the reaction was completed, the ZIF-L nanosheets were separated using a centrifuge at a speed of 5000rpm for 3.0min.

[0069] 2.5g ZIF-L nanosheets were dispersed in an ethanol-water mixed solution (150mL ethanol + 350mL water), stirred for 0.5h, then 0.25g hexadecyltrimethylammonium bromide (CTAB) was added, and stirring continued for 0.5h. In order to allow CTAB to be fully adsorbed on the surface of the ZIF-L nanosheets, 0.4375g resorcinol, 0.149g 4-fluorophenol, 1.25mL28wt% ammonia water were added in sequence, magnetic stirring was continued for 0.5h, and finally 0.64mL 37-40wt% formaldehyde aqueous solution was added with a pipette. The reaction was continued for 8.0h, and a layer of fluorine-doped phenolic resin was coated on the surface of the ZIF-L nanosheets. A sufficient amount of ZIF-L@FPR composite nanosheets was synthesized, separated by vacuum membrane filtration, transferred to a 70℃ oven for drying for 24h, and dried ZIF-L@FPR-3 composite nanosheets were collected. Place it in an open quartz container, transfer it to a tube furnace, and heat it at 5℃min in a nitrogen inert atmosphere. -1 The heating rate was from room temperature to 800° C., kept at 800° C. for 2.0 h, and then naturally cooled to room temperature to obtain a two-dimensional fluorine-doped carbon nanosheet-3. Other implementation steps and methods were the same as those in Example 1.

[0070] Comparative Example 1

[0071] At room temperature, 7.35 g Zn(NO3)2·6H2O was dissolved in 500 mL deionized water, and 16.25 g Hmim was dissolved in 500 mL deionized water. The mixture was stirred magnetically for 0.5 h until fully dissolved. The molar ratio of Zn 2+:Hmim=1:8. The Hmim aqueous solution was quickly poured into the Zn(NO3)2 aqueous solution, and the solution instantly turned milky white. After stirring for 0.5h, a large amount of white floccules appeared, and the total reaction time was controlled at 4.0h. After the reaction was completed, the ZIF-L nanosheets were separated by a centrifuge at a speed of 5000rpm for 3.0min. 3.5g ZIF-L nanosheets were dispersed in an ethanol-water mixed solution (150mL ethanol + 350mL water), stirred for 0.5h, and then 0.35g hexadecyltrimethylammonium bromide (CTAB) was added, and stirring continued for 0.5h. In order to make CTAB fully adsorbed on the surface of the ZIF-L nanosheets, 0.8168g resorcinol and 1.75mL≥28% ammonia water were added in sequence, and magnetic stirring was performed for 0.5h. Finally, 0.90mL 37-40% formaldehyde aqueous solution was added with a pipette. The reaction was continued for 8.0 h, and a layer of phenolic resin (PR) ( Figure 2 B) Synthesize a sufficient amount of ZIF-L@PR composite nanosheets, separate them by vacuum membrane filtration, transfer them to a 70°C oven for drying for 24 h, and collect the dried ZIF-L@PR composite nanosheets. Place them in an open quartz container, transfer them to a tube furnace, and heat them at 5°C min in a nitrogen inert atmosphere. -1 The heating rate was from room temperature to 800°C, kept at 800°C for 2.0 hours, and then naturally cooled to room temperature to obtain a two-dimensional carbon nanosheet. Other implementation steps and methods were the same as those in Example 1.

[0072] Comparative Example 2 (mesoporous fluorine-doped carbon)

[0073] 0.41 g of resorcinol, 0.14 g of 4-fluorophenol and 0.21 g of hexamethylenetetramine were dissolved in 200 mL of deionized water by magnetic stirring, and then 0.40 g of block copolymer Pluronic F127 was dispersed and dissolved in the above solution. The above mixed solution was transferred to a reactor and reacted at 120 ° C for 4 hours to obtain a brick-red suspension. The brick-red particles were separated by centrifugation at 11000 rpm for 10 minutes, and dried at 80 ° C for 24 hours to obtain a brick-red powder. The above brick-red powder was placed in a quartz boat, transferred to a tube furnace, and heated from room temperature at 5 ° C min in a nitrogen atmosphere. -1 The temperature was raised to 350°C at a rate of 100 °C and kept at this temperature for 1 h, and then heated to 800°C and kept at this temperature for 2 h to obtain a mesoporous fluorine-doped carbon material. 1.5 g of mesoporous fluorine-doped carbon material, 1.4 g of additives (BaSO4 and lignin, mass ratio of 6:1), 0.06 g of polyester staple fiber and 100 g of lead powder were mixed in a high-speed shear mixer for 5 min. 13 g of water and 7 g of a density of 1.4 g cm –3Sulfuric acid, stir thoroughly to prepare lead paste, and control the material temperature to be no higher than 65° C. Apply the lead paste to the grid, and obtain the negative electrode plate of the lead-carbon battery after curing and drying. Other implementation steps and methods are the same as those in Example 1.

[0074] according to Figure 1 It can be seen that the preparation process and method of two-dimensional fluorine-doped carbon nanosheets.

[0075] Figure 2 The ZIF-L nanosheets synthesized at room temperature are shown to be elliptical leaf-shaped ( Figure 2 A). After the pure ZIF-L nanosheets were carbonized at 800℃, their morphology was destroyed and could not be maintained ( Figure 2 D). Coating a layer of phenolic resin or fluorine-doped phenolic resin on the surface of ZIF-L ( Figure 2 , B and C), and two-dimensional carbon or fluorine-doped carbon nanosheets were obtained by high-temperature carbonization ( Figure 2 , E and F), the morphology of the ZIF-L hard template is well maintained. The long axis lateral size of the ZIF-L nanosheet is micrometer-level, concentrated in the range of 4 to 8 μm. After carbonization, the size of the composite nanosheet shrinks, but it is still micrometer-scale, concentrated in the range of 3 to 6 μm.

[0076] Apply the lead paste to the topmost grid hole (12.3mm×10.5mm) of the lead strip, and control the total mass of the lead paste to 1.28g. Figures 3-4 As shown, for the negative electrode doped with two-dimensional carbon nanosheets, the redox peak spacing is 0.801V; for the negative electrode doped with two-dimensional fluorine-doped carbon nanosheets, the redox peak spacing is 0.237V. The introduction of fluorine can increase the redox reversibility of Pb / PbSO4 and reduce the internal resistance of the battery. The oxidation peak area of ​​the CV curve is significantly larger than the reduction peak area, indicating that irreversible sulfation is inevitable. The ohmic resistance of the negative electrode doped with two-dimensional fluorine-doped carbon nanosheets is significantly smaller than that of the negative electrode doped with two-dimensional carbon nanosheets.

[0077] Figures 5-6 As shown in Figure 2, compared with two-dimensional carbon nanosheets, the coulombic efficiency, voltage efficiency and energy efficiency of the lead-carbon battery with two-dimensional fluorine-doped carbon nanosheets added to the negative plate are more stable. Figure 7 As shown in the figure, for the lead-carbon battery with two-dimensional carbon nanosheets added to the negative plate, the charge and discharge cycle life is 33 times, which is in sharp contrast to the lead-carbon battery with two-dimensional fluorine-doped carbon nanosheets added to the negative plate, the cycle life is greatly extended to 96 times, which is about 3 times that of the former. It is worth noting that the lead-carbon battery with two-dimensional fluorine-doped carbon nanosheets added to the negative plate had an internal short circuit phenomenon at 97 times and had to stop operating. The experimental results show that the lead-carbon battery with two-dimensional fluorine-doped carbon nanosheets added to the negative plate has better cycle stability.

[0078] Figure 8As shown in Figure 2, many lead sulfate crystals are generated near the surface of the negative electrode containing two-dimensional carbon nanosheets instead of sponge lead ( Figure 8 A), which is also verified by the obvious discharge effect during SEM observation. In sharp contrast, the structure of the sponge lead is mostly preserved in the negative plate containing 2D fluorine-doped carbon nanosheets ( Figure 8 B), mainly due to the suppression of hydrogen evolution reaction and the improvement of electrochemical reversibility of Pb / PbSO4 redox couple. Moreover, in both cases, the sponge lead structure inside the negative plate remains almost unchanged ( Figure 8 , C and D). For both negative plates, the PbSO4 crystal particles are clearly visible near the surface, and the sulfation phenomenon inside is significantly weaker than that on the surface.

[0079] Fig. 9 As shown, the I on the top of the negative electrode plate containing two-dimensional carbon nanosheets and two-dimensional fluorine-doped carbon nanosheets PbSO4 / I Pb were determined to be 13.6% and 11.9% ( Fig. 9 A and B). This indicates that incorporating 2D fluorine-doped carbon nanosheets into the active material of the negative electrode can significantly inhibit the sulfation process.

[0080] Table 1 shows that when preparing two-dimensional fluorine-doped carbon nanosheets, 4-fluorophenol is used to replace the same amount of resorcinol in the raw material.

[0081] Table 2 shows that the charging acceptance current of the lead-carbon battery with the negative plate doped with two-dimensional fluorine-doped carbon nanosheets is significantly higher than that of the two-dimensional carbon nanosheets and mesoporous fluorine-doped carbon nanoparticles.

[0082] As shown in Table 3, fluorine doping inhibits the hydrogen evolution reaction.

[0083] Table 1

[0084]

[0085] Table 2

[0086]

[0087]

[0088] Table 3

[0089]

[0090] The results show that increasing the size of the carbon material as the negative electrode additive of the lead-carbon battery can improve the battery's charge acceptance capacity, promote the electrochemical reduction of PbSO4 to metallic lead, inhibit sulfation, and extend the cycle life of the lead-carbon battery.

[0091] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing two-dimensional fluorine-doped carbon nanosheets, characterized in that: The following steps are involved: a) First, a hard template elliptical metal organic framework ZIF-L nanosheet was synthesized, with a major axis size of about 4 to 8 μm, a minor axis size of about 2 to 4 μm, and a thickness of about 200 to 300 nm, and the nanosheet was dispersed in an ethanol aqueous solution with a volume fraction of 30 to 40 vol%, and a mass concentration of ZIF-L of 7.0 to 9.0 mg mL -1 , adding cationic surfactant, resorcinol, fluorine-containing monomer, ammonia water and formaldehyde solution to the above dispersion, reacting, centrifuging and drying to obtain powder; b) calcining the powder to obtain two-dimensional fluorine-doped carbon nanosheets; The calcination temperature is 800-1000°C (preferably 800-900°C, more preferably 800-850°C), the calcination time is 2-4h (preferably 2-3h, more preferably 2-2.5h), the major axis size is about 3-7μm, the minor axis size is about 1-3μm, and the thickness is about 150-250nm.

2. The preparation method according to claim 1, characterized in that: The cationic surfactant is selected from at least one or more of cetyltrimethylammonium bromide (CTAB), cetyltrimethylammonium chloride, cetylpyridinium bromide, dodecyltrimethylammonium bromide, and tributyl cetylphosphonium bromide; The fluorine-containing monomer is selected from at least one or more of 4-fluorophenol, 3-fluorophenol, 3-(trifluoromethoxy)phenol, and 4-(trifluoromethyl)phenol; The mass ratio of the cationic surfactant, resorcinol, fluorine-containing monomer, 28-30% ammonia water and 37-40% formaldehyde solution is 1:1-2:0.1-1:3-5:1-3 (preferably 1:1-1.5:0.2-0.8:3.5-4.5:1.5-2.5, more preferably 1:1-1.25:0.3-0.7:3.8-4.2:1.75-2.25); the mass ratio of ZIF-L nanosheets to precursor fluorine-doped phenolic resin is 6-8:1 (preferably 6.5-7.5:1, more preferably 6.8-7.2:1).

3. The preparation method according to claim 1, characterized in that: The reaction temperature is 15 to 50°C, and the reaction time is 6 to 10 hours; Preferably, the centrifugal speed is 2000-5000 rpm, and the centrifugal time is 2-10 min; Preferably, the drying temperature is 60-100° C., and the drying time is 24-36 hours.

4. The preparation method according to claim 1, characterized in that: The process of synthesizing the hard template elliptical metal organic framework ZIF-L nanosheet is as follows: 1) Dissolve 5-10 g Zn(NO3)2·6H2O in 400-600 mL deionized water to obtain a Zn(NO3)2 aqueous solution; dissolve 15-20 g 2-methylimidazole (Hmim) in 400-600 mL deionized water to obtain a Hmim aqueous solution; 2) Molar ratio of Zn 2+ :Hmim=1:8; The Hmim aqueous solution and the Zn(NO3)2 aqueous solution were mixed and reacted for 2.0~6.0h, and the ZIF-L nanosheets were separated by centrifugation.

5. A two-dimensional fluorine-doped carbon nanosheet obtained by the preparation method according to any one of claims 1 to 4.

6. Use of the two-dimensional fluorine-doped carbon nanosheet according to claim 5 in a negative electrode plate of a lead-carbon battery.

7. The use according to claim 6, characterized in that: The following steps are involved: Step 1: adding water and sulfuric acid to a mixture containing two-dimensional fluorine-doped carbon nanosheets, additives, short fibers and lead powder, and stirring to obtain a lead paste; Step 2: Press the lead paste onto the grid, solidify it, and dry it to obtain the negative electrode plate of the lead-carbon battery.

8. The use according to claim 7, characterized in that: The mass ratio of the two-dimensional fluorine-doped carbon nanosheets, additives (BaSO4 and lignin, with a mass ratio of 7 to 8:1), polyester staple fibers and lead powder is 1.5:1.4 to 1.6:0.06 to 0.08:100 to 150 (preferably 1.5:1.45 to 1.55:0.065 to 0.075:110 to 140, more preferably 1.5:1.48 to 1.52:0.068 to 0.072:120 to 130).

9. The use according to claim 7, characterized in that: The water accounts for 13% to 20% (preferably 14% to 19%, more preferably 15% to 18%) of the mixture by mass; the sulfuric acid accounts for 7% to 12% (preferably 8% to 11%, more preferably 9% to 10%) of the mixture by mass, and the density of the sulfuric acid at 25°C is 1.4 g cm -3 .

10. The use according to claim 6, characterized in that: The curing temperature is 45 to 55° C., and the curing time is 40 to 60 hours; Preferably, the temperature of the drying I is 60-85° C., the drying time is 9-20 hours, and the thickness of the lead paste is 2-4 mm.

Citation Information

Patent Citations

  • Techniques for low temperature direct graphene growth on glass

    CN108137327A

  • Preparation method and application of lead oxide nanoparticle anchored reduced graphene oxide

    CN115188929A